Neurofibromin 1 mediates sleep depth in Drosophila. - Elizabeth B Brown; Jiwei Zhang; Evan Lloyd; Elizabeth Lanzon; Valentina Botero; Seth Tomchik; Alex C Keene (PLoS Genetics, 2023)
Neural regulation of sleep and metabolic homeostasis are critical in many aspects of human health. Despite extensive epidemiological evidence linking sleep dysregulation with obesity, diabetes, and metabolic syndrome, little is known about the neural and molecular basis for the integration of sleep and metabolic function. The RAS GTPase-activating gene Neurofibromin (Nf1) has been implicated in the regulation of sleep and metabolic rate, raising the possibility that it serves to integrate these processes, but the effects on sleep consolidation and physiology remain poorly understood. A key hallmark of sleep depth in mammals and flies is a reduction in metabolic rate during sleep. Here, we examine multiple measures of sleep quality to determine the effects of Nf1 on sleep-dependent changes in arousal threshold and metabolic rate. Flies lacking Nf1 fail to suppress metabolic rate during sleep, raising the possibility that loss of Nf1 prevents flies from integrating sleep and metabolic state. Sleep of Nf1 mutant flies is fragmented with a reduced arousal threshold in Nf1 mutants, suggesting Nf1 flies fail to enter deep sleep. The effects of Nf1 on sleep can be localized to a subset of neurons expressing the GABAA receptor Rdl. Sleep loss has been associated with changes in gut homeostasis in flies and mammals. Selective knockdown of Nf1 in Rdl-expressing neurons within the nervous system increases gut permeability and reactive oxygen species (ROS) in the gut, raising the possibility that loss of sleep quality contributes to gut dysregulation. Together, these findings suggest Nf1 acts in GABA-sensitive neurons to modulate sleep depth in Drosophila.